STRENGTHENING PHYSICAL ACTIVITY AND MOTOR SKILLS OF VOLLEYBALL PLAYERS - Inomov Faxriddin Urmonjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article considers physical qualities as the basis of the motor capabilities of volleyball players, for physical self-improvement and a healthy lifestyle, expanding the possibilities of developing physical activity in accordance with the needs of students.